1997
DOI: 10.1016/s0196-0644(97)70282-8
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Lidocaine as Adjunctive Therapy in the Treatment of Decompression Illness

Abstract: TOPTwo cases of severe decompression illness for which IV lidocaine was used as adjunctive therapy to recompression and hyperbaric oxygen therapy are described. The first patient demonstrated improvement only after lidocaine was added to her treatment; the second had essentially complete recovery after only a single treatment despite severe symptoms and a significant delay in presentation. These cases support the need for a controlled clinical trial of lidocaine as an adjunct to hyperbaric therapy in decompres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 6 publications
0
5
0
2
Order By: Relevance
“…Lignocaine has been shown to reduce brain dysfunction after air embolism in animal models 34. Several case reports suggest that lignocaine has a beneficial effect on outcome in decompression sickness, even if treatment has been delayed and the symptoms had been previously refractory to recompression 35 36. Putative mechanisms for the efficacy of lignocaine include an anti-leucocyte effect and the deceleration of ischaemic transmembrane ion shifts 37.…”
Section: Prevention and Treatment Of Diving Diseasementioning
confidence: 99%
“…Lignocaine has been shown to reduce brain dysfunction after air embolism in animal models 34. Several case reports suggest that lignocaine has a beneficial effect on outcome in decompression sickness, even if treatment has been delayed and the symptoms had been previously refractory to recompression 35 36. Putative mechanisms for the efficacy of lignocaine include an anti-leucocyte effect and the deceleration of ischaemic transmembrane ion shifts 37.…”
Section: Prevention and Treatment Of Diving Diseasementioning
confidence: 99%
“…Although there are no published randomized trials of lidocaine in humans, anecdotal reports support its use in DCS (12). A sodium channel blocker, lidocaine has been used as a local anes thetic and prophylactic antiarrhythmic agent for ven tricular tachycardia and fibrillation (4).…”
Section: Lidocainementioning
confidence: 99%
“…A rat study found predive intraperitoneal in jections of lidocaine reduced DCS from 72-0% (31). Of the two studies that used lidocaine to treat neurological DCS, one reported no benefit from a 5-h infusion as an adjunct to recompression in a porcine model (7) and the other reported improvement after lidocaine was added during hyperbaric oxygen treatment (12). Low-dose li docaine (2 mg .…”
Section: Lidocainementioning
confidence: 99%
“…La lidocaïne, connue pour ses effets neuroprotecteurs, a largement été étudiée dans les accidents aéro-emboliques cérébraux [28]. Des cas anecdotiques semblent montrer qu'elle pourrait être un complément thérapeutique prometteur dans les ADD médullaires sévères [29]. Les médicaments vasodilatateurs ou modificateurs de la rhéo-logie sont également largement proposés en France de façon empirique.…”
Section: Autres Mesures Thérapeutiquesunclassified